2005
DOI: 10.1002/anie.200300639
|View full text |Cite
|
Sign up to set email alerts
|

Dithiol Proteins as Guardians of the Intracellular Redox Milieu in Parasites: Old and New Drug Targets in Trypanosomes and Malaria‐Causing Plasmodia

Abstract: Parasitic diseases such as sleeping sickness, Chagas' heart disease, and malaria are major health problems in poverty-stricken areas. Antiparasitic drugs that are not only active but also affordable and readily available are urgently required. One approach to finding new drugs and rediscovering old ones is based on enzyme inhibitors that paralyze antioxidant systems in the pathogens. These antioxidant ensembles are essential to the parasites as they are attacked in the human host by strong oxidants such as per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
184
1
4

Year Published

2007
2007
2014
2014

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 299 publications
(190 citation statements)
references
References 216 publications
1
184
1
4
Order By: Relevance
“…Interfering with redox metabolism represents a promising approach to antiparasitic drug development (20) prominent examples being Schistosoma mansoni thioredoxin-glutathione reductase (31) and trypanothione reductase of L. donovani and T.b. brucei (32).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interfering with redox metabolism represents a promising approach to antiparasitic drug development (20) prominent examples being Schistosoma mansoni thioredoxin-glutathione reductase (31) and trypanothione reductase of L. donovani and T.b. brucei (32).…”
Section: Discussionmentioning
confidence: 99%
“…However, compounds inhibiting both, structurally highly related, disulfide reductases simultaneously and inhibitors acting on PfGR in mosquito stages should still be considered as antimalarial strategies. Furthermore, drugs like methylene blue that act as redox-cycling substrates of plasmodial GR or TrxR (18,20) are still very promising.…”
Section: Discussionmentioning
confidence: 99%
“…All of these parasites have in common that the ubiquitous glutathione reductase is replaced by a trypanothione reductase. The flavoenzyme maintains trypanothione (N 1 ,N 8 -bis(glutathionyl)spermidine) and glutathionylspermidine (Gsp) 2 in the reduced state (8,9). The parasite-specific trypanothione is synthesized from glutathione and spermidine in two consecutive steps.…”
mentioning
confidence: 99%
“…[25,26] Trypanosoma cruzi, Trypanosoma brucei and Leishmania major are the human pathogens which cause tropical diseases such as sleeping disease, Chagas disease and leishmaniasis also produce ovothiol A. [27][28][29][30] Elucidation of the corresponding biosynthetic pathway may reveal novel strategies to treat these conditions, for which no efficient therapy is known. Furthermore, identification of the ovothiol A biosynthetic genes (see below) revealed that several plant pathogens such as Erwinia amylophora, the causative agent of fire blight and Phytophthora infestans which causes potato blight, are also ovothiol A producers.…”
Section: Ergothioneine Biologymentioning
confidence: 99%